Pengaruh Pelatihan Komunikasi Asertif pada Perawat Pelaksana yang Mengalami Konflik Interpersonal terhadap Kinerjanya dalam Memberikan Asuhan Keperawatan di Ruang Rawat Inap RSUD Solok: The Effect of Assertive Communication Training on Nurses Experiencing Interpersonal Conflict on Their Performance in Providing Nursing Care in the Inpatient Room at Solok Regional Hospital - Allfar End Honey; Reni Prima Gusty; Yulastri Arif (NERS Jurnal Keperawatan, 2012)
This study aims to determine the effect of assertive communication training on implementing nurse who experience interpersonal conflict on their performance in carrying out nursing care at the IRNA RSUD Solok. This type of research is a quasi experimental approaches one group pretest. Samples in this studies using total sampling technique, with a sample of 24 people. Interpersonal conflict is measured by questionnaires and respondents in providing nursing care was measured using the observation sheet. Were processed using statistical tests homogeneity. Marginal test obtained p = 0.00 ( 0.05 ) this shows there is a significant effect of training assertive communication on the performance of the experienced nurses managing interpersonal conflict in providing nursing care. Suggested to the hospital to provide training of assertive working environment for all nurses in staff development programs in an effort to improve the quality of nursing care in hospitals. Then to research in order investigation with another models in manage conflicts in organization.